(untitled) (Movimenta (ISSN 1984-4298), 2021)
Introduction: Infant development is a combination of neuromotor, sensory and environmental conditions. The initial signs of psychomotor delay are nonspecific, and impairment in any of the sensory inputs can be expressed by atypical motor development. Vision is one of the main sensory inputs for sensory motor learning, and strabismus and ambioplasia stand out among the visual impairments associated with delay. The aims this study was to describe the initial psychomotor development of 4 full-term infants, with congenital strabismus. Case description: Four squint boys (4-18 months) were evaluated using the Denver II Test and Alberta Children’s Motor Scale at three different times, with intervals of 86 ± 34 days between evaluations. All children showed delayed psychomotor development in at least two tests performed. Discussion: Children with congenital strabismus, without a diagnosis of neuromotor abnormalities, showed changes in development. Unfavorable developmental results in strabismus can result from the poor development of binocular vision that impairs spatial and depth perceptions, and can interfere with motor results. Performing instrumented developmental assessments in strabic infants can be an important tool in this monitoring, in order to favor the intervention and minimize future repercussions for the child.